KAJIAN YURIDIS PENGUASAAN TANAH SECARA NOMINEE - I GUSTI AGUS YUDA TRISNA PRAMANA; I WAYAN SUARDANA; I DEWA GEDE BUDIARTA (Universitas Mahasaraswati K. Mataram, 2024)
Land is a place for human habitation as well as being a source of livelihood for those who earn a living through agriculture and ultimately land which is used as the final burial place for someone who dies. Humans can obtain food by utilizing land, apart from that, land also has an emotional relationship with humans. Everyone definitely needs land, not only in life, in the event of death, humans still need land as a resting place. Humans live happily and in abundance if they can use the land they control or own in accordance with applicable natural laws. Humans will be able to live peacefully and peacefully if they can exercise their rights and obligations in accordance with certain limits in the applicable laws that regulate human life in society. Therefore, the need and importance of land ownership rights, however, there is still the practice of ownership of land rights by foreign investors, where legal norms clearly prohibit ownership of land rights by foreign nationals, but with unclear norms that can be used by a person. foreigners borrow names just as Indonesian citizens borrow names, until now this practice is still ongoing. The method used in conducting this research is the normative juridical method where the research refers to statutory regulations. Based on the method used, the government should immediately create regulations that do not overlap and provide legal certainty.